The Role of Digital Personal Selling and Product Innovation with Brand Knowledge as a Mediating Variable in the Decision to Buy a Car from the Honda Brand in Serang City - Vicki Agung Triana; Uli Wildan Nuryanto; Sutisna Sutisna (LPPPIPublishing, 2023)
The purpose of this research is to analyze the role of digital personal selling and product innovation with brand knowledge as a mediating variable in the decision to buy a car from the Honda brand in Serang City. This study uses a quantitative approach. In this study, the group analyzed consisted of customers who had previous knowledge or experience of buying Honda cars in Serang City. 225 people ultimately participated in the study, meaning that their responses were used as a sample. Methods of data analysis using descriptive statistics and inferential statistics. The results of the study show that digital personal selling has a significant effect on brand knowledge from the Honda brand in Serang City. Digital personal selling has a significant effect on the decision n to buy a car from the Honda brand in Serang City. Product innovation has a significant effect on brand knowledge from the Honda brand in Serang City. Product innovation has a significant effect on the decision to buy a car from the Honda brand in Serang City. Brand knowledge has a significant effect on the decision to buy a car from the Honda brand in Serang City. Digital personal selling has a significant effect on the decision to buy a car through mediation of brand knowledge from the Honda brand in Serang City. Product innovation has a significant effect on the decision to buy a car through mediation of brand knowledge from the Honda brand in Serang City.